A Field Trip Report: An Overview of the Paleomorphology and Paleogeography of Tortonian–Messinian Carbonates in the Almería-Níjar Basin, Southern Spain - Minarwan Minarwan (Berita Sedimentologi, 2011)
Southern Spain is famous for its beautiful beaches that usually receive a flock of Spanish and European tourists during the summer. The region has Mediterranean climate without much rain but a lot of sunshine for majority of the year. It has mild and wet winter but in some places it can be very dry and has limited vegetation cover only. The climate is a contributing factor to the preservation of spectacular rock outcrops, which provide beautiful landscapes, outstanding scenes, and more importantly, valuable field laboratory to learn sedimentology and stratigraphy. One such region is Almería Province that has several small basins, including the Almería-Níjar Basin.The Almería-Níjar Basin has extensive outcrops of Upper Miocene carbonate complex that lie on the foothill of Sierra Alhamilla and also along the coast. Recently, a group of geoscientists from Repsol visited some of the Upper Miocene carbonate outcrops to see their large scale geometries and then to get a closer look at their lithofacies. The visit was aimed mainly to observe paleomorphology that can be used as analogs for seismic interpretation purpose. The Upper Miocene carbonate outcrops of the Almería-Níjar Basin are unique because their present geometries are still similar to their paleomorphologies during the time of deposition.